RESPON MASYARAKAT TERHADAP PELAYANAN PERNIKAHAN PASCA PEMBERLAKUAN PERATURAN PEMERINTAH NOMOR 48 TAHUN 2014 TENTANG BIAYA NIKAH (STUDI KASUS DI KUA KEC. SELEBAR KOTA BENGKULU) - Heti, Yurda (UIN Fatmawati Sukarno Bengkulu, 2017)
This research raised problems response the public about free and marriage marriage paid at home in the kecamatan kua largest city bengkulu .The purpose of this study is to find response the public about free and marriage marriage paid at home in the kecamatan kua largest city bengkulu .This research use method juridical empirical , to technique data collection interview, chief and documentation, after data obtained were analysed according to miles and huberman in sugiyono to analyze qualitative may be done by means reduction the data reduction) , presentation of the data display) , conclusion (verification) , so that it can be drawn a conclusion to answer of any the existing problems. The research showed response the public about free marriage in the kecamatan kua largest city bengkulu who gives responnya through chief and interview known that the community kecamatan largest city bengkulu less responding well, this is proven than 100 % the results of the answer informants them do not know with the establishment of pp .48 2014 that marriage at the kua free then the community kecamatan largest city bengkulu does not agree with marriage at the kua although free this is proven from the answers of the informants 86 % does not agree with marriage at the kua and response the public about marriage paid at home welcome positive although must spend money which is not a little .This is proven from the answer chief informants said that they did not mind spent budget of rp .600,000,—when married at home of 94 %, then the community approve marriage outside the kua equal to 100 %